Untreated early childhood caries is a potential disability: policy and programme implications for Africa - Foláyan, Moréniké Oluwátóyìn; Ishola, Adeyinka Ganiyat; Abodunrin, Olunike Rebecca; Ndembi, Nicaise; El Tantawi, Maha (Frontiers in Oral Health, 2025)
Early Childhood Caries (ECC) is a significant oral health condition that impacts children globally. This manuscript's main objective is to explore ECC's impact on children's oral health-related quality of life (OHRQoL) in Africa, and to highlight the policy and programme recommendations to eliminate untreated ECC as a public health threat in Africa. In Africa, ECC poses a significant public health challenge and has the potential to result in functional disabilities in children. A rapid review of the literature focusing on studies from Africa explored the impact of ECC on children's oral health-related quality of life. The three studies that met the eligibility criteria revealed that ECC negatively impacts multiple dimensions of life, including physical health (pain, malnutrition, chewing difficulties), psychological well-being (low self-esteem, stigma), and social functioning (peer relationships, school attendance). Advanced ECC had more pronounced effects, particularly in the symptom and psychological domains. The paper highlights the urgent need to recognise untreated ECC as a disability within public health frameworks in Africa. Policy recommendations include integrating oral health into primary healthcare systems, expanding community-based prevention programmes, incentivising the production of affordable oral health products, and developing school-based education initiatives. Strengthening oral health workforce capacity and enhancing data collection on ECC prevalence is critical for effective policy formulation and resource allocation. Recognising ECC as a potential disability underscores the need for a multi-sectoral approach to address this neglected public health priority and for prioritising actions to eliminate untreated ECC as the International Day of Persons with Disabilities (December 3) is marked.